Comment on 'An explicit reconstruction method for magnetic resonance electrical property tomography based on the generalized Cauchy formula'. (29th June 2018) - Palamodov, V
Abstract: Elementary arguments are given proving the refutations claimed by Nara et al (2017 Inverse Problems 33 105005) of the author's paper (Palamodov 2016 Inverse Problems 32 035003).